Evaluation as an Individual and Organizational Learning Process the Research Experience of the European Project- Edueval - Ulivieri Stiozzi, Stefania (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Adult education services – in Italy and Europe – are strongly in need of an advanced evaluation culture. How may we create the necessary conditions for the educational value of high-quality evaluation to be recognized? What does “evaluate” mean for managersof adult education staff? What organizational and relational dimensions are called into play by evaluation practices? How should evaluation be carried out in training groups, occupational skills programmesand in services providing care for fragile adult subjects? What knowledge disciplines should be included in the education and training profile of evaluators who wish to bring mindfulness and rigour to the implementation of their role? This paper examines the aims and instruments adopted by the European project EDUEVAL, presenting the results of a qualitative study conducted with a purposive sample of official and unofficial evaluators in Italian adult education contexts, and exploring the educational and learning dispositives required to make evaluation a practice motivating and fostering high-quality educational work within an organization.